Etiology of Meningoencephalitis in children aged less than 5 years - Vivek K. Mishra; Tanzeela Khan; Amar Jeet; Om Prakash; Chandrakanta; Ashish K. Srivastava; Sangram Singh; Neelam Pathak; Amita Jain (Wolters Kluwer Medknow Publications, 2024)
Background: The incidence of meningoencephalitis (ME) in India is poorly understood, and the exact etiological diagnosis is often not possible. This study was planned to elucidate the bacterial and viral etiological diagnosis of ME in children less than 5 years of age. Materials and Methods: The present study was conducted in Virus Research and Diagnostic Laboratory (VRDL), Department of Microbiology, King George's Medical University, Lucknow, from July 2020 to June 2022. Serum, cerebrospinal fluid (CSF), and nose/throat swabs were collected from all the enrolled cases of meningoencephalitis in children below 5 years of age and tested for various etiological agents by ELISA and/or real-time PCR. Results: Of 130 enrolled cases, 50 (38.5%) cases tested positive for one or more etiological agents. Etiological agents of ME detected were Japanese encephalitis virus (JEV) (8.46%), adenovirus (6.92%), influenza virus (5.38%), dengue virus (3.85%), Parvo B-19 virus (3.08%), Orientia tsutsugamushi (3.08%), Herpes Simplex Virus-1 (HSV-1) (1.54%), measles virus (1.54%), and Varicella-Zoster Virus (VZV) (1.54%). Rubella virus, Chikungunya virus (CHKV), Mumps virus, Enteroviruses, Parecho virus, John Cunningham virus (JC), BK virus, Nipah virus, Kyasanur Forest Disease virus (KFD), Chandipura virus, Herpes Simplex Virus (HSV-2), SARS CoV-2, N. Meningitides, and H. Influenzae were tested but not detected in any of the cases. Conclusion: We identified the etiological agents in 50/130 (38.5%) suspected ME cases in children less than 5 years of age, using molecular and ELISA-based diagnostic methods. The four most common pathogens detected were JEV, adenovirus, influenza virus, and dengue virus.